Utilizing waste PET plastics derived metal-organic framework catalyst for the hydrodeoxygenation of lignin phenols - Khani, Yasin; Kumar, Avnish; Hwang, Jinwoo; Ko, Chang Hyun; Ha, Jeong-Myeong; Han, Jeong Woo; Park, Young-Kwon (Elsevier BV, 2025)
In this study, the catalytic hydrodeoxygenation (HDO) of guaiacol using polyethylene terephthalate (PET)derived RM125T(p) and TiO2 catalysts (anatase-Ru@TiO2(A), rutile-Ru@TiO2(R), and Ru@TiO2(P25)) under a hydrogen environment was investigated. Comparative analysis of selectivity and yield demonstrates that the M125T(p) support significantly enhances catalytic activity and selectivity. The PET-derived RM125T(p) catalyst exhibited superior performance compared to other catalysts, achieving 100 % guaiacol conversion with 96.7 % selectivity for cyclohexane. This is due to the high porosity, improved Ru dispersion, catalyst oxygen vacancies, hydrogen spillover, and pronounced Lewis acidity, which collectively enhance the rate of adsorption of guaiacol molecules. Furthermore, the RM125T(p) catalyst exhibited extraordinary activity in the HDO of real bio-oils by converting phenolic oxygenates into high-grade hydrocarbons. The HDO reaction results for other model compounds such as phenol, anisole, catechol, and m-cresol, further confirmed the excellent catalytic efficiency of RM125T(p). Additionally, the reused catalyst retained its activity and structural integrity over multiple reaction cycles.